Effects of maternal winter vs. year-round supplementation of protein and energy on postnatal growth, immune function, and carcass characteristics of Bos indicus-influenced beef offspring. (1st March 2022) - Palmer, Elizabeth A; Vedovatto, Marcelo; Oliveira, Rhaiza A; Ranches, Juliana; Vendramini, Joao M B; Poore, Matthew H; Martins, Thiago; Binelli, Mario; Arthington, John D; Moriel, Philipe
Abstract: This 2-yr study evaluated the effects of winter vs. year-round supplementation of Bos indicus -influenced beef cows on cow reproductive performance and impact on their offspring. On day 0 of each year (approximately day 122 ± 23 of gestation), 82 to 84 mature Brangus cows/yr were stratified by body weight (BW; 475 ± 67 kg) and body condition score (BCS; 4.85 ± 0.73) and randomly assigned to 1 of 6 bahiagrass ( Paspalum notatum ) pastures (13 to 14 cows/pasture). Treatments were randomly assigned to pastures consisting of winter supplementation with molasses + urea (WMOL), or year-round supplementation with molasses + urea (YMOL) or wheat middling-based range cubes (YCUB). Total yearly supplement DM amount was 272 kg/cow and supplements were formulated to be isocaloric and isonitrogenous (75% TDN and 20% CP). On day 421 (weaning; approximately 260 ± 24 d of age), 33 to 35 steers/yr were vaccinated against parainfluenza-3 (PI3 ) and bovine viral diarrhea virus type 1 (BVDV- 1) and transported 1, 193 km to a feedlot. Steers were penned according to maternal pasture and managed similarly until slaughter. Data were analyzed using the MIXED and GLIMMIX procedures of SAS. On day 217 (start of breeding season), BCS was greater ( P = 0.01) for YMOL than WMOL cows, whereas BCS of YCUB did not differ ( P ≥ 0.11) to both WMOL and YMOL cows. The percentage of cows that calved, calving date, birth BW, and preweaning BW of the first offspring did not differ ( P ≥ 0.22) among maternal treatments. Plasma cortisol concentrations were greater ( P ≤ 0.001) for YCUB steers at feedlot arrival (day 422) than WMOL and YMOL steers. Moreover, YCUB steers had greater ( P = 0.02) and tended ( P = 0.08) to have greater plasma concentrations of haptoglobin compared to WMOL and YMOL steers, respectively. Antibody titers against PI3 and BVDV-1 viruses did not differ ( P ≥ 0.25) among maternal treatments. Steer BW at feedlot exit was greater ( P ≤ 0.05) for YMOL and WMOL than YCUB steers. However, feedlot DMI did not differ ( P ≥ 0.37) by maternal treatment. Hot carcass weight, yield grade, LMA, and marbling did not differ ( P ≥ 0.14) among maternal treatments. Percentage of steers that graded low choice was enhanced ( P ≤ 0.05) for WMOL and YCUB than YMOL steers. Maternal year-round supplementation of range cubes or molasses + urea either did not impact or decrease growth, immune function, and carcass characteristics of the offspring when compared with maternal supplementation of molasses + urea during winter only.